Systematic review of experimental studies published in “Perspectivas em Análise do Comportamento” from 2010 to 2018 - Keiner, Simone Assunção; Marinho, Vitor Duncan; Malerbi, Fani Eta Korn (Perspectivas em Análise do Comportamento, 2020)
This paper is a systematic review of the experimental articles published in the Brazilian journal Perspectivas em Análise do Comportamento (RPAC) from 2010, when it was created, to 2018. All experimental research has been considered eligible to be analyzed. The 15 selected investigations revealed: (1) very low number of experimental investigations; (2) human beings as the main kind of subjects; (3) preference for intra-subject design and computerized records; (4) prevalence of basic researches; (5) predominance of research involving stimulus equivalence; (6) limited use of inferential statistics; and (7) little attention to generalization, integrity and agreement between observers in applied research. In addition to this preliminary view on the behavior of research by behavior analysts, the data obtained by the present study suggest the need for greater experimental emphasis.